Structural and Emulsifying Properties of Soybean Protein Isolate–Sodium Alginate Conjugates under High Hydrostatic Pressure - Zihuan Wang (MDPI AG, 2021)
Soybean protein isolate (SPI) is a kind of plant derived protein with high nutritional value, but it is underutilized due to its structural limitations and poor functionalities. This study aimed to investigate the effects of high hydrostatic pressure (HHP) treatment on SPI and sodium alginate (SA) conjugates prepared through the Maillard reaction. The physicochemical properties of the conjugate synthesized under 200 MPa at 60 °C for 24 h (SPI–SA–200) were compared with those of the conjugate synthesized under atmospheric pressure (SPI–SA–0.1), SPI-SA mixture, and SPI. The HHP (200 MPa) significantly hindered the Maillard reaction. This effect was confirmed by performing SDS-PAGE. The alterations in the secondary structures, such as α-helices, were analyzed using circular dichroism spectroscopy and the fluorescence intensity was determined. Emulsifying activity and stability indices of SPI-SA-200 increased by 33.56% and 31.96% respectively in comparison with the SPI–SA–0.1 conjugate. Furthermore, reduced particle sizes (356.18 nm), enhanced zeta potential (‒40.95 mV), and homogeneous droplet sizes were observed for the SPI-SA-200 emulsion. The present study details a practical method to prepare desirable emulsifiers for food processing by controlling the Maillard reaction and improving the functionality of SPI.